Virus‐induced phytohormone dynamics and their effects on plant–insect interactions. Issue 4 (19th March 2021) - Pan, Li‐Long; Miao, Huiying; Wang, Qiaomei; Walling, Linda L.; Liu, Shu‐Sheng
Summary: Attacks on plants by both viruses and their vectors is common in nature. Yet the dynamics of the plant–virus–vector tripartite system, in particular the effects of viral infection on plant–insect interactions, have only begun to emerge in the last decade. Viruses can modulate the interactions between insect vectors and plants via the jasmonate, salicylic acid and ethylene phytohormone pathways, resulting in changes in fitness and viral transmission capacity of their insect vectors. Virus infection of plants may also modulate other phytohormones, such as auxin, gibberellins, cytokinins, brassinosteroids and abscisic acid, with yet undefined consequences on plant–insect interactions. Moreover, virus infection in plants may incur changes to other plant traits, such as nutrition and secondary metabolites, that potentially contribute to virus‐associated, phytohormone‐mediated manipulation of plant–insect interactions. In this article, we review the research progress, discuss issues related to the complexity and variability of the viral modulation of plant interactions with insect vectors, and suggest future directions of research in this field.